Effect of economic growth on income inequality, labor absorption, and welfare - Erni Panca Kurniasih (Universitas Islam Indonesia, 2017)
This research aims to analyze the effect of economic growth on income inequality, labor absorption and economic welfare in Indonesian provinces. A 165 observations of panel data was analyzed using path analysis. The result showed that the economic growth has significant negative effect on income inequality in Indonesian provinces but it has no significant effect on both labor absorption and economic welfare. The labor absorption has significant positive effect on income inequality even though it has no significant effect on economic welfare. In addition, the economic welfare is not significantly influenced by the income inequality.